A novel method for work capacity calculation of centrifugal compressor impellers in energy storage systems. (December 2022) - Han, Fenghui; Wang, Zhe; Mao, Yijun; Tan, Jiajian
Abstract: As the basis for centrifugal compressor design, the traditional one-dimensional scheme assumes that there is no flow prewhirl at the impeller inlet (i.e., C 1 u = 0 ) when inlet guide vanes (IGVs) are absent. However, various experiments have proved that a natural prewhirl does exist at the impeller inlet even there is no IGV. In this study, a novel method is proposed to calculate the Euler work of impellers considering the natural prewhirl, and firstly applied to centrifugal compressors without IGVs. Stodola's approach dealing with the slip velocity at the impeller outlet is adopted to the flow at the impeller inlet. A new formula for the Euler work calculation is deduced to evaluate the effect of natural prewhirl on centrifugal impellers. Then, this method is applied in two different model stages of industrial centrifugal compressors to verify against the experimental and numerical data. The results indicate that, compared to the traditional scheme assuming C 1 u = 0, the novel method with modified formula considering the influence of C 1 u ≠  0 is more feasible for high-speed centrifugal compressors. With the aid of the novel calculation method proposed in this paper, the one-dimensional design accuracies of centrifugal compressor stages are improved by 7% compared with the traditional method.